Monitoring Smoothly Degrading Systems for Increased Dependability - Avritzer, Alberto; Weyuker, Elaine J. (Empirical software engineering : an international journal, 1997)
A strategy is presented for determining when it is advantageous to take some action to restore a system to full capacity. A determination is made of the types of data that need to be collected and circumstances under which the strategy is likely to be useful. Production traffic data is presented for a very large industrial telecommunications project, and the strategy is applied. An investigation is made of when the application of the strategy leads to increased system availability and decreased packet loss experienced by users.